Biological physics of the developing embryo - Newman, Stuart (Cambridge University, 2013)
This book shows how physics can be used to analyze the changes that cells and tissues undergo during development. Major stages and components of the biological development process are introduced and analyzed. Full-color throughout, this comprehensive textbook is suitable for graduate and upper-undergraduate courses in physics and biology.